Smart contract disputes and public policy in the ASEAN+6 region - G. R. De En Goh (Цифровое право, 2022)
Smart contracts provide some benefits, such as better facilitation for contracting parties to monitor performance of their obligation and reducing the cost spent monitoring the contract. However, it is critical to understand various limitations of this concept as well as many legal and public policy uncertainties around it. Given the non-existence of an “universal rule” that governs smart contracts, the issues vary from jurisdiction to jurisdiction. The article applies comparative legal method to analyse the legal regulation of smart contracts in ASEAN+6 countries as well as the leading jurisdictions in the sphere of implementing digital technologies in the economy. Due to public policy considerations, there are different scenarios of smart contract development. The possible outlook is that ASEAN+6 countries would not accept smart contract as contract, cryptocurrency as property, and/or enforcing foreign awards that relate to smart contract disputes and/or cryptocurrency. Another possible way out of the deadlock is to govern relations under smart contracts by the UNIDROIT Principles. However, if the parties do not opt for such a solution, the determination of the applicable law will be left to the relevant conflict-of-laws rules with all of the uncertainties. Therefore, the author suggests that supranational laws is the better path for avoiding uncertainties in smart-contractual relationships.